Flow Structure in an Artificial Seagrass Meadow in Combined Wave-Current Conditions - Schaefer, Rachel B.; Nepf, Heidi M. (Frontiers in Marine Science, 2022)
Experiments were conducted in a laboratory flume using an artificial seagrass meadow, modeled after Zostera marina, to examine the impact of waves on the vertical structure of time-averaged current, Reynolds stress, and turbulent kinetic energy (TKE) under combined wave-current conditions. With the addition of smaller waves, defined by a ratio of wave velocity to current velocity Uw/Uc < 2.5, the time-averaged velocity peaked above the meadow, which was similar to pure current conditions. When Uw/Uc > 2.5, the presence of waves caused the time-averaged velocity to peak near the top of the meadow. For Uw/Uc > 1 the presence of waves reduced the magnitude of peak Reynolds stress. For all conditions considered, the wake production of turbulence dominated the shear production of turbulence in the meadow. However, the wave velocity was less efficient than the current velocity in generating TKE in the meadow because the movement of the blades forced by the oscillatory fluid motion reduced the relative velocity between the blades and the wave. A modified hybrid model for wake production of TKE in a flexible canopy under combined wave-current conditions was proposed to account for the relative contributions of waves and currents. Wake production of TKE was dominated by waves when Uw/Uc > 1 and dominated by currents when Uw/Uc < 1. The models and observations proposed in this study contribute to an enhanced understanding of the relative influences of waves and currents on seagrass meadow flow structure in realistic combined wave-current conditions.